Lactoferrin and Immunoglobulin G Concentration in Bovine Milk from Cows with Subclinical Mastitis during the Late Lactation Period - Galfi, Annamaria; Radinović, Miodrag; Milanov, Dubravka; Savić, Sara; Boboš, Stanko; Pajić, Marija (Acta Scientiae Veterinariae, 2016)
Background: Lactoferrin and immunoglobulin G in milk have an important role in udder resistance to infection in the involution period. Both proteins express antimicrobial activity- lactoferrin by the binding and sequestration of iron ion; and immunoglobulin G by complement activation, bacterial opsonization and agglutination. Many factors affect lactoferrin and immunoglobulin G concentrations in bovine milk, such as the stage of lactation, milk production, and intramammary infections. The aim of this study was to determine concentrations of lactoferrin and immunoglobulin G in milk from healthy cows and subclinical mastitic cows during the late lactation period, and to evaluate the relationship between them. Materials, Methods & Results: A total of 150 quarter milk samples from 41 cows (Holstein-Friesian breed) in late lactation period were reviewed in this study. Milk samples were collected during morning milking, using aseptic techniques in sterile test tubes. From each sample, 0.1 mL of milk was plated on Columbia blood agar base with 5% defibrinated ovine blood, MacConkey agar and Sabouraud dextrose agar and incubated for 24 h - 48 h (bacteria) and 5 days (yeasts, mould) at 37oC. Milk samples for detection lactoferrin and immunoglobulin G concentration were skimmed at 1,400 g for 45 min and stored at -20°C until analysis. Lactoferrin concentration in bovine milk was determined using the Bovine Lactoferrin ELISA Quantitation Set. Milk samples were diluted at a ratio of 1:10,000. Plates were read at 450 nm absorbence values. Immunoglobulin G concentration was determined by the immunodiffusion method using radial immunodiffusion (RID) plates. Milk samples were diluted in a ratio of 1:30. Reading of results was done after incubation for 48 h by measuring the diameter of the precipitation ring. The highest mean lactoferrin concentration was observed in udder quarters infected with contagious pathogens (Streptococcus agalactiae and Staphylococcus aureus), while the highest mean immunoglobulin G concentration was detected in milk samples where minor mastitis pathogens (coagulase-negative staphylococci and Corynebacterium spp.) were isolated. Milk samples where Staphylococcus aureus was isolated had the lowest immunoglobulin G concentration, and the lowest lactoferrin concentration was observed in samples infected with enviromental pathogens (Streptococcus dysgalactiae). Discussion: This study showed that lactoferrin and immunoglobulin G concentrations are higher in milk samples from subclinical mastitic cows than in milk from normal lactating cows. Lactoferrin concentrations in milk samples from udder quarters infected with major mastitis pathogens were significantly higher than in milk infected with minor mastitis pathogens. The lowest concentration of immunoglobulin G was detected in milk samples where Staphylococcus aureus was isolated, while the highest immunoglobulin G concentration was observed in milk samples from quarters infected with minor mastitis pathogens. Lactoferrin and immunoglobulin G concentrations were significantly and positively correlated in all milk samples. This means that cows with high lactoferrin concentrations have high immunoglobulin G concentrations. In quarter milk samples infected with Staphylococcus aureus, lactoferrin and immunoglobulin G concentrations were negatively correlated. The cause of these findings could be the suppression of local immune response of mammary gland.